Ekspresi Gen TP53 Pada Kanker Payudara: Implikasi Molekuler Terhadap Respon Terapi dan Pengembangan Pengobatan Presisi - Amalia, Huznul; Mardia HM, Ainun; Hala, Yusminah (Symbiotic: Journal of Biological Education and Science, 2025)
Breast cancer remains the most prevalent malignancy among women worldwide and a leading cause of cancer-related mortality. One of the critical molecular determinants in its pathogenesis is mutation of the TP53 gene, often referred to as the “guardian of the genome” due to its essential roles in cell cycle control, DNA repair, and apoptosis. This study aims to examine TP53 gene expression and mutation patterns in breast cancer and their implications for therapeutic response and precision medicine strategies. A systematic literature review was conducted following the PRISMA guidelines, sourcing articles from Scopus, PubMed, Web of Science, and DOAJ databases published between 2015 and 2024. The findings indicate that TP53 mutations occur in approximately 30% of breast cancer cases, with the highest prevalence in the triple-negative breast cancer (TNBC) subtype. Common hotspot mutations, including R175H and R248Q, result in loss of p53 tumor-suppressor function, resistance to chemotherapeutic agents such as doxorubicin and cisplatin, and activation of the PI3K/AKT pro-survival pathway. Emerging therapeutic strategies—such as p53 reactivators (e.g., APR-246), MDM2 inhibitors, immune checkpoint inhibitors, and CRISPR/Cas9-based gene editing—offer promising avenues for targeted intervention. This review underscores the importance of individualized genomic profiling to optimize breast cancer treatment, particularly in Asian populations.